The effect of continuous venovenous hemofiltration on neutrophil gelatinase-associated lipocalin plasma levels in patients with septic acute kidney injury. Issue 1 (December 2016) - Dai, Xingui; Li, Tao; Zeng, Zhenhua; Fu, Chunlai; Wang, Shengbiao; Cai, Yeping; Chen, Zhongqing
Abstract Background It is known that continuous venonenous hemofiltration (CVVH) does not affect the plasma level of neutrophil gelatinase-associated lipocalin (pNGAL) in acute kidney injury (AKI) patients. However, because of the unique pathophysiology underlying AKI caused by sepsis, the effect of CVVH on pNGAL in this clinical setting is less certain. The purpose of this study was to determine the effect of CVVH on pNGAL in sepsis-induced AKI patients. Methods Between August 1, 2014, and December 31, 2014, 42 patients with sepsis-induced AKI underwent CVVH in the general intensive care unit of our institution and were consecutively enrolled in this study. Prefilter, postfilter, and ultrafiltrate pNGAL measurements were taken at the initiation of continuous renal replacement therapy (CRRT) and repeated after 2, 4, 8, and 12 h (T0, T2h, T4h, T8h, and T12h, respectively). The mass transfer, plasma clearance, and sieving coefficient were calculated based on the mass conservation principle. Results Following CVVH initiation, we found that pNGAL in the ultrafiltrate decreased significantly (P = 0.013); however, levels at the inlet and outlet showed no significant change (P > 0.05 for both). Furthermore, there was no change in the total mass removal rate, total mass adsorption rate, and plasma clearance over time (P > 0.05 for all), and a significant decrease in the sieving coefficient (P = 0.007) was seen. Conclusions The results of this study show a limited effect of CVVH on pNGAL in sepsis-induced AKI patients. This suggests that pNGAL may be used as an indicator of renal progression in these patients. However, a larger study to confirm these findings is needed. Trial registration ClinicalTrials.gov, NCT02536027 . Retrospectively registered on 20th August 2015.